DIVERSITY IN SEVERITY OF HIGH-RESOLUTION COMPUTED TOMOGRAPHY FINDINGS OF COVID-19 PATIENTS WITH DIABETES - ABBAS, S; NISAR, S; HASSAN, MM; SAMAD, M; HAIDAR, FA; ABBAS, A (Biological and Clinical Sciences Research Journal, 2024)
COVID-19 patients with diabetes mellitus present a unique subset, often experiencing more severe disease due to their compromised immune status and chronic inflammatory state. Objectives: The current study aimed to see the diversity in HRCT findings in COVID-19 patients with diabetes, aiming to elucidate the extent and nature of pulmonary involvement in this high-risk group. Methods: This retrospective study included 134 diabetic patients, and the data was collected from the patient records unit. BMI was categorized according to World Health Organization criteria, and glycemic control was evaluated based on hemoglobin A1c (HbA1c) levels. Additionally, waist circumference, hip circumference, and waist-hip ratio were measured. Lipid profile parameters were also analyzed, including serum cholesterol, low-density lipoprotein (LDL), triglycerides, and high-density lipoprotein (HDL). The duration of diabetes was categorized into two groups: <10 years and ≥10 years. Finally, the diversity in the patient characteristics was seen using the HRCT findings. Results: Most of the study patients were female (66.41%). The mean BMI was 24.37±4.11. BMI categories were as follows: underweight (BMI <18.5) in 8.02% of patients, healthy weight (BMI 18.5-24.9) in 32.83% of patients, overweight (BMI 25-29.9) in 26.86% of patients, and obese (BMI ≥30) in 32.08% patients. The mean HbA1c level was 9.02±1.89. Glycemic control was categorized as good in 43 patients (32.08%) and poor in 91 patients (67.91%). The mean waist circumference was 82.88 ± 12.41 cm, the hip circumference was 92.0 ± 10.71 cm, and the waist-hip ratio was 0.91 ± 0.13. The mean serum lipid levels were as follows: cholesterol 181.0 ± 7.70 mg/dL, LDL 145.50 ± 21.56 mg/dL, triglycerides 195.75 ± 18.10 mg/dL, and HDL 39.51 ± 5.76 mg/dL. Patients were categorized by the duration of diabetes diagnosis: <10 years in 110 patients (36.7%) and ≥10 years in 190 patients (63.3%). Conclusion: The study highlights the critical need for personalized clinical management of COVID-19 patients with diabetes. By understanding the specific HRCT patterns and underlying pathophysiological mechanisms, healthcare providers can improve the prognosis and outcomes for this disease group.